Cholesterol granuloma in the neck – a case of vocal fold paralysis - Sara Raquel Azevedo; José Ricardo Brandão; Mariline Santos; Miguel Bebiano Coutinho; Cecília Almeida e Sousa (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Introduction: The aim of this study was to report a case of cholesterol granuloma in the neck with vocal cord paralysis.